Description of Prionchulus jonkershoekensis n. sp. (Nematoda: Mononchida), a new predatory species from South Africa - van Rensburg, Candice Jansen (J Nematol, 2021)
Prionchulus jonkershoekensis n. sp. is described from South Africa and illustrated using morphological, morphometric, and molecular techniques. This species is characterized by its body length (1.78–2.14 mm); the size of buccal cavity (38–44 × 24–31 µm), lower dorsal tooth position in relation to buccal cavity base, the position of amphidial aperture just above dorsal tooth apex, pars proximalis vaginae with almost straight walls, and tail 144–158 µm long with sickle shaped posterior third part. Phylogenetic analyses based on 18 S rDNA and 28 S rDNA of P. jonkershoekensis n. sp. revealed close relationships of the new species with Prionchulus punctatus and Prionchulus muscorum. This is also an additional geographical record for the genus from South Africa.